Fiscal Policy Changes in Namibia: Are Namibians Better Off After Independence? (The Strategic Review for Southern Africa, 2020)
An attempt is made in this article to examine the effect of new policy instruments implemented by the self-governing Namibia on the aspects of human development. We analysed whether the changes in fiscal policy adopted in postindependence era have improved the quality of life of Namibians as compared to pre-independence era. Time series data on government expenditures as well as health and education related indicators for the period 1980 to 2015 has been used for the purpose of analysis. Impacts of per capita government expenditure on healthcare and education on reduction in mortality, increase in life expectancy at birth, rising literacy and growth of people acquiring higher education/technical education have been examined. During 1980 to 1990, Namibia was under South African control, a colonial era, and, therefore, in the 1991 to 2015 period Namibia was independent. The study reveals that Namibians are better off in the post-independence as compared to the colonial era on major parameters. However, changes in policy have not been successful in transforming the lives of Namibians to the levels expected. There is still ample scope for improvement in the fiscal management of the country.
Keywords: Policy Instruments; Healthcare; Education; Human Development; Namibia; South Africa